Religious Faith And The Types Of Rationality - Jasiński, Karol (Studia Theologica Varsaviensia, 2019)
The purpose of this article is to determine the nature of religious faith and various types of rationality, with special emphasis on instrumental rationality, to characterise the link between faith and reason, and to reveal the insufficiency of instrumental reason in the sphere of faith. Instrumental reason is limited to the practical pursuits, which forces man to rely on a different type of mental activity in other spheres of life, such as religiousness. The paper is divided into three parts. The first section presents the nature of religious faith (religious faith as a psychological attitude of the followers and as a set of theses accepted in a given religion; existential and cognitive dimension of faith; the relationship between faith and revelation; assertion of religious truth). The second section outlines the nature of modern rationality (pluralism of rationality, its types, instrumental reason). The third section focuses on the relationship between religious faith and human reason (ratio, substantial reason, intellect).